Teoretyczne zagadnienia standardów w prawodawstwie w stosowaniu prawa - Wróblewski, Jerzy (Wydział Prawa i Administracji UAM, 1989)
The term „legal standard" is polysemiec and fuzzy in all languages related with law. The author singles out five basic uses of the term in question: (SP-1) standard as a legal rule;(SP-2) standard as a general clause; (SP-3) standard as an evaluation, (SP-4) standard as a legal principle; (SP-5) a technological standard. Each type of the singled out standard is analyzed. The standards SP-1, SP-2, SP-3 and SP-4 are interconnected and have a „family resemblance", whereas SP-5 stands apart, because the former group functionally serves the elasticity of law-applying decisions, and SP-5 restricts the variety of technology and its products by fixing quantitative requirements. The use of SP-1 is related to the conceptual identification of a legal rule. SP-2 involves various constructions of general clauses, which are either identified with SP-2 or SP-2 appears as a sub-class of the clauses in question. SP-3 implies axiological conceptions of values polarized in the opposition of cognitivism and noncognitivism. SP-4 is linked with different constructions of the principle of law and especially with the widely discussed comparison of rules and principles. Standards are linked with the choice of law-making technique which usually is a compromise between following the natural common language and shaping a precize artificial language. An use of standards delegates to the law-applying agencies the power to determine the solution of concrete cases. The discussion of the role of standards in application of law is based on the analysis of the normal formulas of the fractional decisions of the application of law (decision of validity, of interpretation, of evidence, of choice of consequences). The standards could function as applied rules, as directives of the application of law and as values justifying decisions. The way of using the standards depends not only on the formulation of applield legal texts but also on the accepted ideology of the application of law.
Theoretical problems of standards in law-making and application of law